EFFICACY OF RIBOSOMAL COMPLEX IN EPSTEIN-BARR VIRAL INFECTION IN CHILDREN - S.N. Orlova; S.A. Mashin; S.V. Zhambarov ("Paediatrician" Publishers LLC, 2011)
Article contains study results of clinical efficacy of ribomunil in complex treatment and rehabilitation program in 30 children, recovered from acute Epstein-Barr viral infection, with disbiosis of nasal, oropharyngeal and colon mucosa. It has been shown that application of ribosomal complex over 1 to 6 months allows successful sanitization of main body loci, it also promotes normalization of blood parametres, decrease general sensitization of the body and thus prevent Epstein-Barr viral infection from becoming chronic and decrease the amount of intercurrent diseases in children. Key words: Epstein-Barr viral infection, disbiosis of main body loci, ribomunil, children. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 41-47.)